Chemical Constituents and Evaluation of Cytotoxic Activities of Curcuma zedoaria (Christm.) Roscoe Oils from Malaysia and Indonesia. Issue 4 (4th July 2017) - Syamsir, Devi Rosmy; Sivasothy, Yasodha; Hazni, Hazrina; Abdul Malek, Sri Nurestri; Nagoor, Noor Hasima; Ibrahim, Halijah; Awang, Khalijah
Abstract: The essential oils obtained by hydrodistillation of the rhizomes of Curcuma zedoaria (Christm.) Roscoe collected from Malaysia and Indonesia were analyzed by capillary GC and GC-MS. Both the oils were principally sesquiterpenic in nature and were characterized by zerumbone (17.14% and 12.07%, respectively). Camphor (17.56% and 19.69%, respectively) was also abundant in both oils. The cytotoxic effects of both the oils on human breast (MCF-7 and MDA-MB 231), lung (A549 and SK-LU-1) and cervical (HeLa S3 and SiHa) cancer cell lines were examined using the MTT assay. The Malaysian C. zedoaria rhizome oil was found to be cytotoxic against the MCF-7, SK-LU-1, HeLa S3 and SiHa cell lines, with IC50 values being less than 10 μg/mL. Our findings support the use of the Malaysian C. zedoaria rhizome oil as a potential chemopreventive agent towards a wide spectrum of cancer in particular cervical cancer.